Silicon Optrode with a Micromirror‐Tip Providing Tunable Beam Profile During Infrared Neuromodulation of the Rat Neocortex - Horváth Ágoston Csaba; Mórocz Ákos; Csomai Borbála; Szabó Ágnes; Balogh-Lantos Zsófia; Fürjes Péter; Tóth Estilla Zsófia; Fiáth Richárd; Fekete Zoltán (ADVANCED MATERIALS TECHNOLOGIES, 2024)
Infrared (IR) neuromodulation holds an increasing potential in brain research, which is fueled by novel neuroengineering approaches facilitating the exploration of the biophysical mechanism in the microscale. The group lays down the fundamentals of spatially controlled optical manipulation of inherently temperature‐sensitive neuronal populations. The concept and in vivo validation of a multifunctional, optical stimulation microdevice is presented, which expands the capabilities of conventional optrodes by coupling IR light through a monolithically integrated parabolic micromirror. Heat distribution in the irradiated volume is experimentally analyzed, and the performance of the integrated electrophysiological recording components of the device is tested in the neocortex of anesthetized rodents. Evoked single‐cell responses upon IR irradiation through the novel microtool are evaluated in multiple trials. The safe operation of the implanted device is also presented using immunohistological methods. The results confirm that shift in temperature distribution in the vicinity of the optrode tip can be controlled by the integrated photonic components, and in parallel with the optical stimulation, the device is suitable to interrogate the evoked electrophysiological activity at the single neuron level. The customizable and scalable optrode system provides a new pathway to tailor the location of the heat maximum during infrared neural stimulation.